The Implementation of Article 76 Paragraph (1) of Government Regulation Number 39 of 2023 in Toll Road Development in Seyegan District, Sleman Regency - Maria Hutapea; Krisna Ginang Wirawan; Patricia Eva Christi Situmorang; Athar Prana Abdi; Rizal Syahputra Siadary (Westscience Press, 2026)
This article is based on empirical legal research conducted in 2026 on compensation in the construction of the Jogja-Bawen toll road in Seyegan District, Sleman Regency, Yogyakarta Special Region. In the implementation of land acquisition for toll road development, issues often arise regarding compensation. Article 76 paragraph (1) of Government Regulation Number 39 of 2023 states that “forms of compensation can be provided in the form of money, replacement land, resettlement, share ownership, or other forms agreed upon by both parties.” The main issue is how the application of Article 76 paragraph (1) of this Government Regulation affects former owners. The implementation of Article 76 paragraph (1) of Government Regulation Number 39 of 2023 for former landowners in the Jogja-Bawen toll road development is in the form of money. There was no discussion or agreement in determining the form and amount of compensation because it was directly decided by the government. This compensation is not advantageous for former landowners who have replacement land to build a new house. Another impact is that the principles of sustainability and humanity are not realized.